Konsep Pendidikan Ruhani Perspektif Hadis: Studi dengan menggunakan Pendekatan Tematik - Intan Pujiani (Gunung Djati Conference Series, 2023)
Various cases of juvenile delinquency such as brawls, free sex, acts of violence and various criminal cases are so prevalent in the country Spiritual education is the main education, mental education so that faith is maintained and avoid negative actions. This study aims to discuss the concept of spiritual education from the perspective of hadith. This research is a qualitative type using the syarah and takhrij hadith methods. The results and discussion in this article are that there are concepts of spiritual education such as multiplying dhikr and its virtues in the book of Sahih Bukhari number 6856, by fasting on the moon is contained in the book of Sahih Muslim number 1942, and tazkiyatun nafs is contained in Musnad Ahmad bin Hanbal nomor 24575 This study concludes that in the hadith of the Prophet there is a concept of spiritual education that will help the general public in improving their spiritual education.